Aggressive esthesioneuroblastoma with divergent differentiation: A taxonomic dilemma. (1st November 2016) - Charles, Norman C.; Petris, Carisa K.; Kim, Eleanore T.
ABSTRACT: The authors describe an esthesioneuroblastoma (olfactory neuroblastoma) that occurred within the nasal cavity and brain in a 31-year-old man. Following excision, the tumor recurred in the left orbit and in mediastinal lymph nodes. Treatment included orbital excision and systemic chemotherapy. Histopathology showed a high-grade neuroepithelial tumor with positive immunohistochemical markers for neuroendocrine and epithelial components, an unusual combination raising issues concerning taxonomy.